Anti-bacterial activity of rosella flowers extract (Hibiscus sabdariffa linn) in inhibiting bacterial growth methicillin-resistant Staphylococcus aureus - Zinatul Hayati; Winda Yulia; T. Fadrial Karmil; Abdullah Azmy (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2012)
Infections caused by bacteria Methycillin Resistant Staphylococcus aureus (MRSA) has become a worldwide health problem because of its increasing incidence. Rosella flower (Hibiscus sabdariffa Linn) has been known to have efficacy as an antibacterial. The purpose of this study is to determine the antibacterial activity of rosella flower extract in inhibiting the growth of MRSA. This study is an experimental research laboratory using rosella flower extract as a treatment, vancomycin as a positive control and distilled water as negative control. Fresh and dried rosella flowers crushed and then macerated with 96% ethanol for 24 hours. The filtrate obtained was concentrated by rotary evaporator at a temperature of 35 ˚ C-40 ˚ C and then diluted to a concentration of 12.5%, 25%, 50% and 75%. Phytochemical test is then performed. S.aureus bacteria isolated from clinical specimens in RSUDZA. Test of the antibacterial activity of rosella flower extract performed using Kirby Bauer disc diffusion method. Parameters on the disc were measured in millimeters MRSA. The data obtained were statistically analyzed and grouped into categories of Greenwood (1995). Phytochemical test results indicate the presence of rosella flower extract contains flavonoids, tannins, saponins, triterpenoids and alkaloids. Test results of the inhibition of rosella flower extract concentration of 12.5%, 25%, 50% and 75% of the growth of MRSA each inhibitory zone formed with an average diameter of 14.2 mm, 19.2 mm, 22.8 mm and 24.18 mm, whereas the positive control and negative control respectively of 19.8 mm and 5 mm. The results of data analysis showed that the ethanol extract of rosella flowers significant effect in inhibiting the growth of MRSA by the value of p 0.05. Based on the criteria of Greenwood, rosella flower extract ethanol concentration of 50% and 75% belong to the category of strong inhibitory power in inhibiting the growth of MRSA, a concentration of 25% falls into the category of being and the concentration of 12.5% falls into the category of weak. The results can be concluded that rosella flower ethanol extract can inhibit the growth of MRSA.